Natural history of silent aspiration on modified barium swallow studies in the pediatric population. (October 2019) - Shay, Elizabeth O.; Meleca, Joseph B.; Anne, Samantha; Hopkins, Brandon
Abstract: Objectives: To investigate the natural history of silent aspiration in the pediatric population. Methods: Retrospective chart review of patients (age < 3 years) who underwent modified barium swallow studies (MBSS), between January 1, 2007, to December 31, 2017, were studied to compare comorbidities and determine course of resolution in those with silent aspiration. Results: A total of 148 charts were reviewed. Patients that underwent surgical intervention for laryngeal anomalies causing silent aspiration and those with overt aspiration or oral aversion were excluded. Of the 56 patients in the study, 25 had silent aspiration and 31 demonstrated no silent aspiration on MBSS. There was a higher rate of overall comorbidities amongst silent aspirators (96.0% vs. 48.4%, p=0.003) in comparison to patients with no silent aspiration on MBSS. Silent aspirators had higher rates of cerebral palsy (16.0% vs. 0%, p=0.034), and seizures (36.0% vs. 3.2%, p=0.003). Of the 20 patients with silent aspiration with an MBSS completed beyond the initial one, 13 (65.0%) experienced resolution, 5 (20.0%) did not experience resolution by age 5, and 2 (10.0%) had unknown resolution due to being lost to follow up or not yet reaching age 5. No statistically significant associations were found between comorbidities, gender, presence of a gastrostomy tube and resolution. Conclusions: Silent aspiration in children is associated with neurological comorbidities, particularly cerebral palsy and seizures. More than half of the patients with silent aspiration spontaneously resolve over time. Expectant management, close surveillance, and clinical assessments can be considered in these patients on an individual basis.